The Effect of Customer Experience Towards Engagement in Soco by Sociolla - Febilincia, Siti Dzulqadah; Nasution, Reza Ashari (SBM ITB, 2020)
Abstract. Though usage of m-commerce is increasing, the engagement for the platform is low. This research aims to optimize engagement through variable that influences customer experience. Data gathering is done through online survey and use PLS SEM method to analyze the final data. Based on the result of 407 respondents, customer experience has a significant effect towards engagement. Though, customer experience will have stronger effect towards engagement through satisfaction. The most influential antecedents in customer experience is Telepresence. The more immersed the customers in an app, the more it brings to positive customer experience. The findings provide managerial implications for marketers in multi-channel retail, specifically in beauty industry, who uses m-commerce as their channel to set strategy in optimizing customer experience and engagement in mobile application.Keywords: Customer experience; engagement; satisfaction; m-commerce; mobile applicationAbstrak. Meskipun penggunaan m-commerce meningkat, engagement untuk platform ini masih cukup rendah. Penelitian ini bertujuan untuk mengoptimalkan engagement melalui variabel yang mempengaruhi customer experience. Pengumpulan data dilakukan melalui survei online dan menggunakan metode PLS SEM untuk menganalisis data akhir. Berdasarkan hasil dari 407 responden, customer experience memiliki pengaruh yang signifikan terhadap engagement. Akan tetapi, pengalaman pelanggan akan memiliki efek yang lebih kuat terhadap keterlibatan melalui kepuasan. Faktor yang paling berpengaruh dalam pengalaman pelanggan adalah Telepresence. Semakin banyak pelanggan terikat dalam suatu aplikasi, semakin banyak membawa pengalaman pelanggan yang positif. Temuan ini memberikan implikasi manajerial bagi pemasar di multi-channel retail, khususnya di industri kecantikan, yang menggunakan m-commerce sebagai saluran mereka untuk mengatur strategi dalam mengoptimalkan pengalaman pelanggan dan keterlibatan dalam aplikasi mobile.Kata kunci: Aplikasi seluler; customer experience; engagement; kepuasann; m-commerce